1999
DOI: 10.1046/j.1365-2036.1999.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of a 1‐day high‐dose quadruple therapy for cure of Helicobacter pylori infection

Abstract: There is at present clear evidence that Helicobacter pylori is the main aetiologic agent of most gastritis (type B gastritis) and peptic ulceration. Eradication of infection leads to resolution of the gastritis and to spectacular decreases of duodenal and gastric ulcer relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
15
2
Order By: Relevance
“…Eight were excluded from further analysis; [34][35][36][37][38][39][40][41] the reasons for exclusion are outlined in Table 1. All studies compared triple vs. quadruple therapy for H. pylori eradication.…”
Section: Resultsmentioning
confidence: 99%
“…Eight were excluded from further analysis; [34][35][36][37][38][39][40][41] the reasons for exclusion are outlined in Table 1. All studies compared triple vs. quadruple therapy for H. pylori eradication.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, 7-day PPI plus standard bismuth triple therapy, which is now termed quadruple therapy , provides a consistently high eradication rate (approximately 96%) [10,16]. Several short-duration regimens for cure of H. pylori infection have been reported [2,3,[18][19][20][21][22][23][24]. Furthermore, this therapy has fewer adverse effects than commonly observed with 14-day bismuth triple therapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…It was unclear in some of the included studies whether the patients were H. pylori treatment-naive, which might have affected responses to the protocols (Moshkowitz et al, 1999). In addition, some sample sizes were too small to be persuasive (Wermeille et al, 1999;Huo et al, 2006). It was reported that randomization with an adequate number of subjects increases the likelihood that groups will have similar background risks (Fischbach et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…If a higher frequency of re-infection is encountered in the long term, the primary scheme should seriously be questioned, and a more suitable approach with persistent H. pylori eradication is preferred. Some trials had extremely low eradication rates with standard 7-d triple protocols (Wermeille et al, 1999;Zhang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation